Impact of Land Use on Urban Heat Island Phenomenon: A Spatial Analysis of Pare-pare City, South Sulawesi - Nasrul, Nasrul; Maru, Rosmini; Rasul, Mat; Rifaldi.R, Rifaldi.R; Wahyuni, Rara Sri; Faizin, Syuura Annisa; Nuryadi, Nuryadi (Jambura Geoscience Review, 2025)
Urban Heat Island is a phenomenon where surface temperatures are higher in urban areas than in rural areas. One of the cities that experienced this phenomenon was the city of Pare-pare, which was caused by the conversion of vegetation land into settlements due to rapid population growth. This study aims to determine the influence of land use on the Urban Heat Island phenomenon in Pare-pare City. The methods used include spatial analysis and descriptive analysis, secondary data collection in the study was obtained from the Indonesian Geospatial portal and Google Earth Engine and using ArcGis 10.8 software in conducting spatial analysis. The results of the analysis show that there are relationships such as Soreang, Ujung, West Bacukiki and also the north of Bacukiki District which experiences the Urban Heat Island phenomenon due to dense settlements and many road networks. Areas with land cover in the form of settlements and roads have higher surface temperatures than areas with high land cover in the form of vegetation such as the southeastern part of Bakkiki District. The impact of Urban Heat Island is that it causes a decrease in air quality and excessive energy use. The recommended mitigation is the implementation of environmentally friendly infrastructure such as greening around buildings, green roofs, and small parks. The results of this study can be used as useful information for the government in making sustainable spatial planning policies and to evaluate development to reduce the impact of Urban Heat Island.